2016
DOI: 10.21767/2476-1974.100010
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Immunoglobulin Therapy in a Woman with Spontaneous Pregnancy Loss and Multiple Sclerosis

Abstract: Background: Off-label use of intravenous immunoglobulin has been reported for the treatment of recurrent spontaneous pregnancy loss and selected cases of multiple sclerosis.However, the use of subcutaneous immunoglobulin has not been reported in these settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…In a case report, Carbone et al [3] have demonstrated an innovative approach to immunomodulation in women with recurrent pregnancy loss and immunological abnormalities. Although the safety and efficacy of this approach needs further evaluation in large clinical trials, the authors have successfully demonstrated the tolerability and clinical efficacy of subcutaneous immunoglobulin therapy for unexplained abortion and multiple sclerosis.…”
mentioning
confidence: 99%
“…In a case report, Carbone et al [3] have demonstrated an innovative approach to immunomodulation in women with recurrent pregnancy loss and immunological abnormalities. Although the safety and efficacy of this approach needs further evaluation in large clinical trials, the authors have successfully demonstrated the tolerability and clinical efficacy of subcutaneous immunoglobulin therapy for unexplained abortion and multiple sclerosis.…”
mentioning
confidence: 99%